URBAN HERITAGE RESURRECTION: CREATIVE PUBLIC SPACE AS ECONOMIC CATALYST AND TOURISM SUPPORT IN KOTA TUA, JAKARTA - Briano Gautama, Ezra
Every city has its own history that then forms the identity of a city and thus differentiate itself from other cities. With how rapid the development of a city is due to globalization, city identity is increasingly fading and historical areas are often neglected. Development is often centered on the city's economy and neglects the cultural elements of a city. Jakarta like other cities has its own historical areas, one of which is Kota Tua. Due to the grim condition of the buildings and public infrastructure there, the government has made various efforts to improve the quality of this area so that it can once again become the icon of DKI Jakarta. There have been several businesses that reuses old buildings and gave them a new function. However, there has not been any concentrated effort that can create a momentum for significant economic development in Kota Tua. Designing buildings with new functions can be a driving force that could create the momentum needed for an economic development in Kota Tua. There lies a huge potential generated by the large number of tourists who visit Kota Tua. A design project that will create a new icon in Kota Tua needs to have a design strategy. One can just reuse old buildings and renovate the interior, but to make a statement there needs to be a contrast from the present image of Kota Tua and that is to design a new building in such a way that still creates harmony with the surrounding context. The concept of contextual design becomes the answer to these problems. By applying this concept, designers can present designs that are novel but still have a connection with local identities or characteristics. Apart from the form, the program of the building also needs to be considered if you want to fulfill the purpose of creating a new icon of the area. Commercial and creative functions were brought up for this design project, looking from a similar project namely M Bloc Space where creative spaces supported by commercial activities can revive dead areas of a city. However, all the existing problems that lie are still unable to be answered with such solutions. The dynamic and vulnerable trends of youth activities are influenced by many factors and are bound to shift overtime. An analysis is then carried out to intervene the issue, which is then answered by presenting a flexible architectural design. This architectural flexibility is expected to provide answers to these problems by becoming a resilient container against the uncertainty of the future. Contextual design and flexible design with commercial and creative functions are the backbone of this design project. This fictional design project is located on Jl. Pintu Besar Utara, Kota Tua, West Jakarta with a sjte area of 4000m2. This project is assumed to be part of the directives of the DKI Jakarta Provincial Government in an effort to revitalize the Kota Tua area. This project will provide three main programs, commercial, exhibition and cultural heritage conservation. The project site is located in the existing Pusat Konservasi Cagar Budaya laboratory building so that this program needs to be reinstated. The exhibition function is presented to answer the current art exhibition trends in which many of the younger generation are starting to have a strong sense of appreciation for art that resulted in the increased market for this type of activity. The exhibition facility is divided into two sections, which are the exhibition space and the auditorium. While the commercial function is presented as a supporting function and as a support for tourism in Kota Tua in general. Broadly speaking, this project aims to support tourism and stimulate the local economy to help improve the quality of the area in general.